A poesia da negatividade: a poética de Paul Celan sob o olhar teórico de Walter Benjamin - Jorge Benedito de Freitas Teodoro (2018)
This study aims to investigate Paul Celans (1920-1970) poetics under Walter Benjamin's (1892-1940) theoretical gaze. In order to do so, we will gauge, through a comparative analysis, what both autors consider history, memory and language. We intend, thereby, to make a reading of the Celanian poetry as poetry of negativity, priorizing its negative aspect, unlike readings that highlight appeasement or synthesis of violence in his work. Thus, in the development of this study, the typical tension in Benjamin's thoughts assumes a determinant importance, for the presence of history in Celan is understood through the distinction between the historicism of the winners and a historical model that claims the presence of barbarism. The mark of memory, in its turn, resembles the outlines of Benjaminian theory as it engage in a dinamic between the necessity of remembering those who are dead and the fight against the voracity of oblivion. As to language, we see an irremediable duality between the mother tongue (Muttersprache) and the murderers tongue (Mördersprache) in the composition of the Celanian counter-word (Gegenwort) that, after all, radically diverges itself from the transcendentality of language intended by Benjamin. Along this path, the primacy of negativity stands out as a conducting wire of the dialog between poet and thinker.